Genetic evaluation for egg mass in partial periods and complete period in meat quails - Ribeiro,Jeferson Corrêa (2012)
The objective of this study was to obtain estimates of genetic and phenotypic parameters for egg mass of meat quails and also to propose an optimal age for selection of birds through the egg mass. The data used in this study came from 3,503 female meat quails (UFV1: 1.811 quails; UFV2: 1.692 quails) of the Poultry Breeding Program from Universidade Federal de Viçosa. The traits examined were egg mass in partial periods until 77, 112, 147 and 182 days, and egg mass in the total period of 407 days by the use of single and bi-trait animal models. For the genetic group UFV1, the heritability values for the periods were high: 0.58, 0.59, 0.57, 0.59 and 0.24 (until 77, 112, 147,182 and 407 days, respectively). The values of genetic correlations were medium, ranging from 0.51 (77 and 407 days) to 0.61 (112 and 407, 147 and 407 days). For the genetic group UFV2, the estimates of heritability were of low magnitude: 0.05, 0.03, 0.04, 0.05, and 0.11 (until 77, 112, 147, 182, and 407 days, respectively). The values for genetic correlation ranged from 0.61 (112 and 407 days) to 0.93 (77 and 407 days). For the genetic group UFV1, the second partial period (112 days) for selection of meat quails using the egg mass trait is recommended, due to a higher value of heritability and a higher value of genetic correlation with the total and relative efficiency close to the unity in this period. In the genetic group UFV2, the first partial period (77 days) is indicated, since it had a higher estimation of genetic correlation and a higher relative efficiency. The choice of these partial periods reduces the generation interval, increasing the intensity of selection and an increase in genetic gain per unit of time.